EXPERIENCES OF SINGLE MOTHERS IN THE LABOUR MARKET; COMPARATIVE STUDY IN ALBANIA AND BOSNIA HERZEGOVINA - Bimbashi, Eliona Kulluri; Marcic, Sinisa (European Scientific Journal, ESJ, 2015)
The level of unemployment in the whole region of the Western Balkans is very high considering the average unemployment rate in the European Union. The majority of all citizens, men and women alike, encounter difficulties in the labor market. Single mothers are no exception. The purpose of the study was to investigate the main determine factors that obstacle women – single mothers in particular entering in the labour market. The methodology was a qualitative one, through conducting focus groups with single mothers and in depth interviews with key informants. The results of the study show that single mothers face several difficulties to enter in the labor market that relate mainly to the lack of child care services, adequate employment and welfare policies, effective support services, etc.